Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/iae.0000000000001982
|View full text |Cite
|
Sign up to set email alerts
|

The Oasis Mp-1 Substudy

Abstract: Substudy results suggest that fixation and sensitivity parameters tended to be better in the ocriplasmin group than in the sham group over time. The substudy identified parameters that were distinct between patients with and without vitreomacular adhesion resolution, suggesting that microperimetry warrants further study as a relevant biomarker for visual function.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Previously, we reported on a substudy of subjects from the OASIS trial who underwent MP to better understand the impact on visual function. 9 This MP sub study only included 27 subjects, but demonstrated a consistently better sensitivity in ocriplasmin treatment patients. However, a transient reduction in sensitivity in the ocriplasmin group was noted at week 1 and month 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported on a substudy of subjects from the OASIS trial who underwent MP to better understand the impact on visual function. 9 This MP sub study only included 27 subjects, but demonstrated a consistently better sensitivity in ocriplasmin treatment patients. However, a transient reduction in sensitivity in the ocriplasmin group was noted at week 1 and month 1.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are very much in line with previously reported electrophysiologic and microperimetric findings. 9 Our study is not without limitations, including most notably the loss of subjects over time which was by virtue of the design of the study which permitted subjects who did not experience release of traction to be exited and undergo vitrectomy or other procedures per their treating physician. The loss of subjects was especially problematic in the sham group where most patients did not demonstrate a spontaneous release.…”
Section: Discussionmentioning
confidence: 99%